2006
DOI: 10.1086/505221
|View full text |Cite
|
Sign up to set email alerts
|

A Study in a Community in Brazil in Which Cutaneous Larva Migrans Is Endemic

Abstract: CLM is a common parasitic skin disease in this rural community, with different topographic patterns of lesions in children and adults. CLM is associated with considerable morbidity. The length of the track can be used to estimate the duration of infestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 25 publications
3
60
0
5
Order By: Relevance
“…Feliz Deserto consists of several typical resource-poor communities (town centre and hamlets). Socioeconomic characteristics have been described elsewhere [17]. The communities are served by the Brazilian Unified Health Care System (SUS) and the so-called Family Health Programme.…”
Section: Study Area and Populationmentioning
confidence: 99%
“…Feliz Deserto consists of several typical resource-poor communities (town centre and hamlets). Socioeconomic characteristics have been described elsewhere [17]. The communities are served by the Brazilian Unified Health Care System (SUS) and the so-called Family Health Programme.…”
Section: Study Area and Populationmentioning
confidence: 99%
“…Algengt er að kláðinn versni á nóttunni og valdi því að sjúklingur eigi erfitt með svefn, líkt og átti sér stað í þessu tilfelli. 9 Vitað er um tilfelli þar sem kláðinn kom ekki fram fyrr en nokkrum mánuðum eftir útsetningu. 10 Lirfan getur skriðið allt frá nokkrum millimetrum á dag til tveggja sentimetra á dag.…”
Section: áGripunclassified
“…The most commonly affected sites are those in close contact with the soil (Araújo et al, 2000). A recent case series of CLM in Brazil, for example, showed that cutaneous lesions are more frequently observed on the feet (73.3%), buttocks (14.7%), genital and inguinal areas (8.0%), legs (2.7%), and hands (1.3%) (Jackson et al, 2006). Other sites, such as the face (Bouchad et al, 2000) and the scalp (Guimarães et al, 1999), are rarely affected.…”
Section: Cutaneous Larva Migransmentioning
confidence: 99%